Enhancing research productivity through bibliometric analysis: A community service training for academics - Purwanto, Edi (Penamas: Journal of Community Service, 2025)
Academics often face challenges in effectively navigating and analyzing the vast and growing body of scientific literature, which limits their ability to identify collaboration opportunities and emerging research trends. This study highlights developing and implementing a community service program to enhance academics' research productivity through bibliometric analysis training. Conducted online on September 6, 2024, the program gathered 34 lecturers and researchers from diverse fields. The training comprehensively introduced bibliometric concepts and practical applications, utilizing tools such as VOSviewer and Scopus Analyze. Participants gained skills in processing bibliographic data, mapping collaboration networks, and identifying emerging research trends. The initiative improved participants' understanding of bibliometric techniques and empowered them to enhance research quality and productivity. Positive feedback from participants underscores the program's success and potential to drive broader academic impact.